Sex, drugs and superbugs: The rise of drug resistant STIs - Alex Broom; Michelle Peterie; Damien Ridge; Lise Lafferty; Katherine Kenny; Jennifer Broom; Angela Kelly-Hanku; Carla Treloar; Tanya Applegate (SSM: Qualitative Research in Health, 2023)
Antimicrobial resistance (AMR) presents a swiftly advancing challenge to a wide range of healthcare and health promotion practices. While rising rates of AMR share some dimensions across contexts, the specificities of field, practice, place and population shape – and at times hinder attempts to stem – the rising tide of this health threat. Sexually transmitted infections (STIs) are one area of healthcare where the threat of AMR has traditionally been met with lethargy. In this paper, we draw on a range of stakeholder perspectives across practice, innovation and regulatory systems in Australia, the US and the UK to understand and examine the evolving nexus of STIs and AMR, including the roles of cultural reception, professional practice and political traction. We argue for a critical sociology of the nexus of sexual health and evolving resistance, which will be instructive for comprehending inaction and informing future developments. We also note that part of this critical sociology must involve challenging stigma concerning sexual practices and people/groups, and recognising the role of communities in driving positive change.